A study on the impact of visual images in advertising media regarding social issue in Malaysia / Nurulhafizah Halid - Halid, Nurulhafizah (2015)
The main goal of the project is to explore the impact of visual images in advertising media regarding social issue in Malaysia. An in depth analysis of the three chosen campaign is conducted. I concentrated on visual images and investigate what intended meanings are created by the visual and how audiences interpret the message. The qualitative research performed in order to obtain data for comparison that is for confirmation or denial of the findings analysis.